2020
DOI: 10.1038/s41598-020-73367-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of omentum-preserving versus resecting gastrectomy for locally advanced gastric cancer with propensity score analysis

Abstract: Omentectomy is conducted for advanced gastric cancer (AGC) patients as radical surgery without an adequate discussion of the effect. This study was conducted to reveal the impact of omentum-preserving gastrectomy on postoperative outcomes. AGC patients with cT3 and 4 disease who underwent total or distal gastrectomy with R0 resection were identified retrospectively. They were divided into the omentum-preserved group (OPG) and the omentum-resected group (ORG) and matched with propensity score matching with mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 36 publications
(36 reference statements)
1
51
0
Order By: Relevance
“…Furthermore, several retrospective studies showed that OPG does not increase the recurrence rate and worsen the survival of patients with GC compared with GCO (3, 5, 10). Sakimura Y et al (11) reported that the recurrence rates of OPG and GCO groups are not different and that omentectomy is not required for radical gastrectomy. Seo WJ et al (5) and Ri M et al (10) reported no survival difference between OPG and GCO in patients with GC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, several retrospective studies showed that OPG does not increase the recurrence rate and worsen the survival of patients with GC compared with GCO (3, 5, 10). Sakimura Y et al (11) reported that the recurrence rates of OPG and GCO groups are not different and that omentectomy is not required for radical gastrectomy. Seo WJ et al (5) and Ri M et al (10) reported no survival difference between OPG and GCO in patients with GC.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of this study was the assessment of the RFS rate of OPG in patients with GC. Ultimately, three studies (3,9,11) reported the 3-year RFS rates, and the meta-analysis of pooled analysis showed no significant difference in the 3-year RFS rate between OPG and GCO groups (OR = 1.40, 95% CI = 0.86 to 2.27, p = 0.18) (Figure 5C). Four studies (3,5,8,10) reported the 5-year RFS rates, and the meta-analysis of pooled analysis showed that the 5-year RFS rates of the two groups were similar (OR = 1.21, 95% CI = 0.95 to 1.55, p = 0.12) (Figure 5D).…”
Section: Oncological Outcomesmentioning
confidence: 99%
See 3 more Smart Citations